MOLECULAR CHARACTERIZATION OF URANIUM(VI) SORPTION COMPLEXES ON IRON(III)-RICH ACID MINE WATER COLLOIDS - Ulrich K.U.; Rossberg A.; Foerstendorf H.; Z?nker H.; Scheinost A.C. (My University, 2006)
A mixing of metal-loaded acid mine drainage with shallow groundwater or surface waters usually initiates oxidation and/or hydrolysis of dissolved metals such as iron (Fe) and aluminum (Al). Colloidal particles may appear and agglomerate with increasing pH. Likewise chemical conditions may occur while flooding abandoned uranium mines. Here, the risk assessment of hazards requires reliable knowledge on the mobility of uranium (U). A flooding process was simulated at mesocosm scale by mixing U-contaminated acid mine water with near-neutral groundwater under oxic conditions. The mechanism of U-uptake by fresh precipitates and the molecular structure of U bonding were determined to estimate the mobility of U(VI). Analytical and spectroscopic methods such as Extended X-ray Absorption Fine-Structure (EXAFS) spectroscopy at the Fe K-edge and the U LIII-edge, and Attenuated Total Reflectance Fourier Transform Infrared (ATR-FTIR) spectroscopy were employed. The freshly formed precipitate was identified as colloidal two-line ferrihydrite. It removed U(VI) from solution by sorption processes, while surface precipitation or structural incorporation of U was not observed. EXAFS data suggest a mononuclear inner-sphere, edge-sharing complex of U(VI) with ferrihydrite in the absence of dissolved carbonate. By employing a novel EXAFS analysis method, Monte Carlo Target Transformation Factor Analysis, we could for the first time ascertain a 3-D configuration of this sorption complex without the necessity to invoke formation of a ternary complex. The configuration suggests a slightly tilted position of the adsorbed UO22 + unit relative to the edge-sharing Fe(O, OH)6 octahedra. In the presence of dissolved carbonate and at pH ?8.0, a distal carbonate O-atom at ?4.3 ? supports formation of ternary U(VI)-carbonato surface complexes. The occurrence of these complexes was also confirmed by ATR-FTIR. However, in slightly acidic conditions (pH 5-6) in equilibrium with atmospheric CO2, the U(VI) sorption on ferrihydrite was dominated by the binary complex species {triple bond, long}Fe(O)2{double bond, long}UO2, whereas ternary U(VI)-carbonato surface complexes were of minor relevance. While sulfate and silicate were also present in the mine water, they had no detectable influence on U(VI) surface complexation. Our experiments demonstrate that U(VI) forms stable inner-sphere sorption complexes even in the presence of carbonate and at slightly alkaline pH, conditions which previously have been assumed to greatly accelerate the mobility of U(VI) in aqueous environments. Depending on the concentrations of U(VI) and carbonate, the type of surface complexes may change from binary uranyl-ferrihydrite to ternary carbonato-uranyl-ferrihydrite complexes. These different binding mechanisms are likely to influence the binding stability and retention of U(VI) at the macroscopic level.
Keywords: ACID MINE DRAINAGE; FTIR SPECTROSCOPY; GROUNDWATER POLLUTION; HYDROLYSIS; MOLECULAR ANALYSIS; OXIC CONDITIONS; OXIDATION; PH; PRECIPITATION (CHEMISTRY); RISK ASSESSMENT; SORPTION; URANIUM